Upholding God’s Rule: Early Muslim Juristic Opposition to the State Employment of non-Muslims - Yarbrough, Luke (Islamic law and society, 2012)
Abstract This is a study of what purport to be the earliest opinions that Muslims expressed about the employment of non-Muslim administrators by an Islamic state. Matn-cumisnād analyses are performed on three early reports which claim that the caliph ʿUmar b. al-Khaṭṭāb instituted a religious criterion for state employment. These constitute the only credible evidence that such a criterion might have been part of administrative policy in the pre-Marwānid period. They were also an important basis for later legal doctrines that forbade the state employment of non-Muslims. The matn-cum-isnād analyses are placed in juxtaposition to historical reports concerning the late Umayyad period, in order to advance the thesis that the reports are likely to have been put into circulation by proto-Sunnī Arab traditionists in second-/eighth-century Kufa in reaction to state policies, particularly those of the Umayyad governor Khālid al-Qasrī.